Instrumentation system for data acquisition and monitoring of hydroponic farming using ESP32 via Google Firebase - Prisma Megantoro; Rizki Putra Prastio; Hafidz Faqih Aldi Kusuma; Abdul Abror; Pandi Vigneshwaran; Dimas Febriyan Priambodo; Diaz Samsun Alif (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
This article discusses the design of a hydroponic planting process monitoring system based on the internet of things. This device uses an ESP32 microcontroller board as the main controller. The parameters that were monitored and acquired were the conditions of the hydroponic growing media. Those parameters are; water pH, water temperature, water turbidity level, and ambient air temperature and humidity. The five parameters are measured by analog sensors integrated with the ESP32. These parameters affect the growth process and the quality of crop yields. This article also describes the calibration method for each sensor used for parameter measurement. Then the monitoring of these parameters is carried out by utilizing a real-time database, namely Google Firebase. This platform is very suitable for all IoT-based monitoring and control applications. Measurement result data is uploaded and saved to the real-time database. Then paired by Android-based applications. This application was created to be used by hydroponic farmers who use this device. Thus the results of monitoring can be used to optimize the process of growing hydroponic plants.